1997
DOI: 10.1007/bf03168691
|View full text |Cite
|
Sign up to set email alerts
|

Variation of monitor luminance on radiologist productivity in the interpretation of skeletal radiographs using a picture archiving and communication system

Abstract: This is el US gOA'glTlltl(2llt work. Th 91 91 llo restrictions on its ltAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A low luminance has been stated to increase the time for diagnosis. 1 Krupinski et al 12 found no significant difference of performance between high and low luminance, although the dwell time was longer with the lowerluminance displays. In another study, it was stated that observers were taking more time to make less accurate decisions using the color display.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A low luminance has been stated to increase the time for diagnosis. 1 Krupinski et al 12 found no significant difference of performance between high and low luminance, although the dwell time was longer with the lowerluminance displays. In another study, it was stated that observers were taking more time to make less accurate decisions using the color display.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, medical-grade monochrome displays are usually recommended, mostly because of their higher luminance. 1 The major drawback of the monochrome displays is their very high cost, which has prompted some institutions to use standard color displays, which are considerably less expensive because they are mass-produced for the general computer market.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative balance between monitor light output and background reporting room lighting is an important factor in determining the degree of radiologist fatigue, as well as efficiency and accuracy [8]. Reiner et al assessed the impact of luminance in interpreting radiographs and found a subjective increase in the observed level of confidence of interpretation as monitor brightness increased [9]. Furthermore, monitor brightness was inversely proportional to reporter fatigue [9].…”
Section: Introductionmentioning
confidence: 99%
“…Reiner et al assessed the impact of luminance in interpreting radiographs and found a subjective increase in the observed level of confidence of interpretation as monitor brightness increased [9]. Furthermore, monitor brightness was inversely proportional to reporter fatigue [9]. On-off light switches should be located near each workstation, ideally with individual dimmers to enable users to adjust the lighting depending on the task being performed [3].…”
Section: Introductionmentioning
confidence: 99%